Bounding Volume Hierarchies for Collision Detection - Hamzah Asyrani Sulaiman; Abdullah Bade (InTechOpen, 2012)
In virtual environment world, performing collision detection between various 3D objects requires sophisticated steps to be followed in order to properly visualize their effect. It is challenging due to the fact that multiple objects undergo various motion depending on the application’s genre. It is however an essential challenge to be resolved since it’s many use in the computer animation, simulation and robotic industry. Thus, object intersection between rigid bodies has become one of the most important areas in order to bring realism to simulation and animation.